Perubahan Pola Penyebaran Kadar Air Media Tanam Arang Sekam dan Pertumbuhan Tanaman Kangkung Darat (Ipomoea reptans Poir.) pada Pemberian Air Secara Terus Menerus dengan Irigasi Tetes - Asep Sapei; Irma Kusmawati (Jurnal Keteknikan Pertanian, 2003)
Drip/trikle irrigation is an irrigation method, which gives high efficiency, high effectivity and assuraes high productivity/yield. This method, is often used for hortivulture and vegetable. The objectives of this research is to study the effect of drip irrigation by continuous water application using 1 and 2 emitters on water distribution and crop growth.The result show that irrigation water by using 2 emitter was spread horizontally more, gave taller crops and more leaves that that using 1 emitter. In general, the effect of continuous water application was beter than intermittent water application.